Implementation of Sustainable Development Goals in MGM China, Macau for Transformations - Yeung, Shirley Mo Ching (Journal of Ecohumanism, 2025)
The aim of this paper is to explore the key elements for transformative entertainment business with sustainable development goals (SDG), art cultureal elements and technology via co-branding. Based on a recent qualitative study on MGM Sustainability Report Analysis by the author with literature search between 2020 and 2023 using the key words related to sustainability and brand buidling. After reviewing the sustainability reports of 4 years, text search of key words by using n’vivo showed the highest frequency are : sustianable development goals implementations - 2079 references, art tourism with impacts - 753 references, and operating labelling - 576 references. A reflection approach has been adopted for the 2049 Macau show of Zhang Yimou and MGM Macau showed the shared values on cobranding with SDG#5, #9 and #17 with humanistic design of SDGs and innovative of AI. The integration of AI into the creative process not only enhances an emerging and emersive way to express traditional cultural contents but also reflects the key elements of transformative leadership and critical success factors of projects related to SDG#3 wellness, SDG#5 gender equality, SDG#8 decent jobs and #9 innovatons. For the use of technology, like artificial intelligence (AI) and blockchain (BC) technology, there is a rising business and new services in the entertainment business and space use. However, these elements are seldom studied for improving the cobranding in cretive art and cultural activities for business and social impacts. With these findings, industry professionals on cobranding with shared values need to re-think the process on identifying partners for sustainable business.